Injuries to the Aorta, Aortic Annulus, and Left Ventricle During Transcatheter Aortic Valve Replacement: Management and Outcomes. (January 2017) - Langer, Nathaniel B.; Hamid, Nadira B.; Nazif, Tamim M.; Khalique, Omar K.; Vahl, Torsten P.; White, Jonathon; Terre, Juan; Hastings, Ramin; Leung, Diana; Hahn, Rebecca T.; Leon, Martin; Kodali, Susheel; et al.
Abstract : The experience with transcatheter aortic valve replacement is increasing worldwide; however, the incidence of potentially catastrophic cardiac or aortic complications has not decreased. In most cases, significant injuries to the aorta, aortic valve annulus, and left ventricle require open surgical repair. However, the transcatheter aortic valve replacement patient presents a unique challenge as many patients are at high or prohibitive surgical risk and, therefore, an open surgical procedure may not be feasible or appropriate. Consequently, prevention of these potentially catastrophic injuries is vital, and practitioners need to understand when open surgical repair is required and when alternative management strategies can be used. The goal of this article is to provide an overview of current management and prevention strategies for major complications involving the aorta, aortic valve annulus, and left ventricle. Abstract : Supplemental Digital Content is available in the text.